Process optimization and characterization on ultrasonication and microwave-assisted phenolic compounds extraction of Ficus Vasta leaves - Wondifraw Abate Abera; Shimelis Kebede Kassahun; Anteneh Marelign Beyene; Shegaw Ahmed Mohammed (Applied Food Research)
Phenolic and flavonoid compounds were extracted from Ficus vasta leaves using ultrasonic and microwave-assisted extraction techniques. For the two chosen extraction techniques, the parameters of the Ficus vasta leaf extraction process was frequency, solute-to-solvent ratio, microwave power, and time. In terms of ratio, power, and time, the optimum microwave-assisted extraction process parameters were 0.075 g/mL, 480 watts, and 60 min, respectively. The extract has a maximum total phenol and flavonoid content of 152.5 mg/g and 75.9 mg/g, respectively. However, the extraction procedure assisted by ultrasonication provided a maximum total phenolic content of 214.9 mg/g and a flavonoid content of 87.8 mg/g extract at an optimal solute-to-solvent ratio of 0.075 g/mL, frequency of 50 kHz, and time of 60 min. The functional groups of phenolic compounds, flavonoids, gallic acid, fatty acids, and other significant components were identified by the use of the Fourier infrared spectrum to characterize the leaf extract. The extract contains possible sources of flavonoids, phenolic compounds, and esters, according to the UV-Vis absorbance of light intensity at wavelengths of 254 nm, 283 nm, and 309 nm. The extract's pH was determined to be 4.6 ± 0.8. Using gas chromatography-mass spectroscopy, the elemental components of the raw leaf powder were also examined, yielding crucial details about the extract. 4-pentanal (0.897%), 4-vinyl phenol (1.119%), 2-methylene-N-phenyl methoxy-1cyclopentanone (0.12%), 3,4,5-trihydroxy benzoic acid (0.824%), and limonene (1.26%) were among the phenolic and ester compounds found in the leaf extract. In conclusion, the extraction technique of ultrasonication pretreatment was found to be efficient and faster, with the yield of phenolic and flavonoid significantly influenced by time and power factors.